1994
DOI: 10.1111/j.1365-2141.1994.tb05109.x
|View full text |Cite
|
Sign up to set email alerts
|

Human resident peritoneal macrophages: phenotype and biology

Abstract: Macrophages represent the primary line of host defences in the peritoneal cavity. In order to study the metabolic activity and maturation stage of human resident peritoneal macrophages (PM phi). peritoneal fluid (PF) was taken by Douglas puncture from healthy hyperstimulated infertile women undergoing oocyte retrieval for in vitro fertilization. Peritoneal fluid and macrophage culture fluids were studied for different inflammatory mediators such as interleukin-1 (IL-1), tumour necrosis factor (TNF) and interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…2B, right panel). IL-6 production by pMU has been documented before [14] and this was dramatically elevated in pMU from peritonitis patients [15]. These data suggest that pMU may perhaps not be as polarized as in vitro generated MU2, but, nevertheless, they do have the high IL-10-producing capacity typical of MU2, suggesting a potential anti-inflammatory activity.…”
Section: Resultsmentioning
confidence: 60%
“…2B, right panel). IL-6 production by pMU has been documented before [14] and this was dramatically elevated in pMU from peritonitis patients [15]. These data suggest that pMU may perhaps not be as polarized as in vitro generated MU2, but, nevertheless, they do have the high IL-10-producing capacity typical of MU2, suggesting a potential anti-inflammatory activity.…”
Section: Resultsmentioning
confidence: 60%
“…In a previous study, we reported that human A-M⌽ and GM-CSF-induced monocyte-derived macrophages (GM-M⌽) are resistant to hydrogen peroxide (H 2 O 2 ) via their high basal and inducible levels of catalase activity and that M-CSF-induced monocyte-derived macrophages (M-M⌽) are sensitive to low levels of H 2 O 2 with low levels of catalase activity (2). GM-M⌽ is phenotypically identical to A-M⌽, whereas M-M⌽ closely resembles peritoneal M⌽ in respect to morphology, cell surface antigen expression, and several biological functions (2)(3)(4)(5)(6)(7). In vivo A-M⌽ express BCL-2 family proteins such as BCL-2 and BCL-X L that prevent H 2 O 2 -induced apoptosis via inhibition of caspase-3 or -9 activation and cytochrome c release from mitochondria (8 -11).…”
Section: Human Tissue Macrophages (M⌽)mentioning
confidence: 99%
“…Table II lists several resident Ms and their tissue specificity. Macrophages comprise the vast majority (>90%) of the white blood cells in the peritoneal cavity, and are considered the first line of defense for the immune system in the abdomen [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%